Amyloid, tau, and astrocyte pathology in autosomal-dominant Alzheimer’s disease variants: AβPParc and PSEN1DE9 - Lemoine L; Gillberg PG; Bogdanovic N; Nennesmo I; Saint-Aubertlfis L; Viitanen M; Graff C; Ingelsson M; Nordberg A (NATURE PUBLISHING GROUP, 2022)
Autosomal-dominant Alzheimer’s disease (ADAD) may be associated with atypical amyloid beta deposits in the brain. In vivo amyloid imaging using 11C-Pittsburgh compound B (PiB) tracer has shown differences in binding between brains from ADAD and sporadic Alzheimer’s disease (sAD) patients. To gain further insight into the various pathological characteristics of these genetic variants, we performed large frozen hemisphere autoradiography and brain homogenate binding assays with 3H-PiB, 3H-MK6240-3H-THK5117, and 3H-deprenyl for detection of amyloid fibrils, tau depositions, and activated astrocytes, respectively, in two AβPParc mutation carriers, one PSEN1ΔE9 mutation carrier, and three sAD cases. The results were compared with Abeta 40, Abeta 42, AT8, and GFAP immunostaining, respectively, as well as with Congo red and Bielschowsky. PiB showed a very low binding in AβPParc. A high binding was observed in PSEN1ΔE9 and in sAD tissues but with different binding patterns. Comparable 3H-THK5117 and 3H-deprenyl brain homogenate binding was observed for AβPParc, PSEN1ΔE9, and sAD, respectively. Some differences were observed between 3H-MK6240 and 3H-THK5117 in ADAD. A positive correlation between 3H-deprenyl and 3H-THK5117 binding was observed in AβPParc, while no such correlation was found in PSEN1ΔE9 and sAD. Our study demonstrates differences in the properties of the amyloid plaques between two genetic variants of AD and sAD. Despite the lack of measurable amyloid fibrils by PiB in the AβPParc cases, high regional tau and astrocyte binding was observed. The lack of correlation between 3H-deprenyl and 3H-THK5117 binding in PSEN1ΔE9 and sAD in contrast of the positive correlation observed in the AβPParc cases suggest differences in the pathological cascade between variants of AD that warrant further exploration in vivo.